2002
DOI: 10.1001/archotol.128.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Removal and Reinsertion in Pediatric Patients

Abstract: No major long-term complications were identified in the patients after MRR. Cephalometric analysis revealed minor abnormalities in 2 children, but no plate migration or bony resorption was identified in the removed and reinserted maxillae. No abnormal development patterns were detected on physical examination or when cephalometric measurements were compared with age- and race-matched normative data. Although further study is warranted, MRR seems safe and effective for treatment of pediatric patients with anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Other modifications of the lateral rhinotomy approach have been reported, such as maxillary removal and reinsertion [11]. This study reported the use of this approach in five children between 11 and 15 years of age.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other modifications of the lateral rhinotomy approach have been reported, such as maxillary removal and reinsertion [11]. This study reported the use of this approach in five children between 11 and 15 years of age.…”
Section: Discussionmentioning
confidence: 97%
“…A variety of approaches have been described to approach the pterygopalatine fossa. Standard approaches suggested in the literature include lateral rhinotomy with a maxillectomy, facial degloving with midface disassembly, Caldwell-Luc approach, and endoscopic transnasal approach [6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative examination of the pediatric MRRI patients confirmed normal visual acuity and extraocular motions in all cases; no complaints of diplopia were encountered. Facial symmetry, assessed by examination of the maxillary alveolar arches, malar projection, and zygomatic arch width, showed that no grossly appreciable growth disturbances had occurred 6 …”
Section: Discussionmentioning
confidence: 99%
“…However, it may affect facial growth due to extensive softtissue dissection and multiple osteotomies as shown in Fig. 8 [27,28]. The frontotemporal craniotomy approach is used in stage IVA tumors according to Andrew et al classification [12,29].…”
Section: Surgical Management Of Jnamentioning
confidence: 99%
“…Fig. 8 Maxillary bone removal and reinsertion [28] Endoscopic surgery for JNA Since advances in endoscopic technology, endoscopic approaches are used as an adjunct to combined approaches, and in some studies, endoscopic removal is the primary method of excision even with dural and cavernous sinus extensions of the tumor.…”
Section: Surgical Management Of Jnamentioning
confidence: 99%